How Does AI Support Substance Abuse Treatment? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Substance abuse and addiction represent a significant global health challenge, affecting millions of people and placing a heavy burden on healthcare systems ...
Keywords: AI in Mental Health; Support; Substance; Abuse; Artificial Intelligence; Machine Learning; Healthcare